Mating, but Not Male Accessory Gland Products, Changes Female Response to Olfactory Cues in Anastrepha Fruit Flies - Córdova-García, Guadalupe; Sirot, Laura; Abraham, Solana; Díaz-Fleischer, Francisco; Flores-Estevez, Norma; López-Ortega, Maurilio; Pérez-Staples, Diana (Frontiers in Physiology, 2021)
Copulation and/or ejaculate components can alter female physiological state and female post-mating behavior. The objective of the present study was to determine if copulation and male reproductive accessory gland fluids (MAGs) modify the behavior of female Anastrepha ludens (Loew) and Anastrepha obliqua (Macquart) (Diptera: Tephritidae) in response to two stimuli: male-emitted pheromone and oviposition host volatiles. Olfactometry studies revealed that mated females of both A. ludens and A. obliqua have a stronger response for host volatiles compared to unmated females, which have a stronger response for male pheromone. We also examined olfactory responses of females mated to testectomized males who could transfer MAGs but not sperm. In both species, MAGs alone did not cause the change in the olfactory response observed after copulation, unlike what has been found in Ceratitis capitata (Wiedemann). Females mated to testectomized males responded equally to the male sex pheromone or to host volatiles, thus suggesting that the whole ejaculate is needed to elicit the complete behavioural switch in olfactory response. The function of MAGs is still unknown in these two pests of economic importance. The response for host volatiles by mated females has implications for the development of baits and traps that should preferably attract and target this population.